The Influence Of Product Quality, Service Quality And Sales Promotion On Toyota Avanza Car Purchase Decisions At Auto 2000 Pramuka Central Jakarta - Putri Nada Lathifah Lathifah; Resti Hardini; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
This study aims to determine the effect of product quality, service quality and sales promotion on purchasing decisions for Toyota Avanza at AUTO 2000 Pramuka, Central Jakarta. This study uses primary data with data collection methods through questionnaires distributed to 100 respondents. The data analysis technique was using inferential analysis with multiple linear regression and using the Statistical Product and Service Solution (SPSS) version 23.0 program. From the research results, it can be seen that product quality (X1) has a positive and significant influence on purchasing decisions, this is shown from the t-test where the t- count value is 2.668 > 1.660 ttable and significant is 0.009 (0.009 < = 0.05), then H0 is rejected. and Ha accepted,. Service Quality (X2) from the results of the study is shown from the tcount, which is 2.613 > 1.660 ttable and the significance is 0.010 (0.010 < = 0.05), then H0 is rejected and Ha is accepted, meaning that Service Quality has a positive and significant effect on Purchase Decisions. Sales Promotion (X3) from the results of this study can be seen in the tcount value of 3.111 > 1.660 ttable and significant 0.000 (0.000 < = 0.05) then H0 is rejected and Ha is accepted, so it can be concluded that Sales Promotion has a positive and significant effect on Buying decision. Thus, it can be concluded that product quality, service quality and sales promotion variables influence purchasing decisions together.